Ruang Lingkup Manajemen Pendidikan Islam - Anis Zohriah; Hikmatul Faujiah; Adnan Adnan; Muhammad Shofwan Mawally Nafis Badri (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Management is an activity capability or skill which includes setting, as well as organizing which has the goal of achieving educational activities effectively and efficiently. Thus, for educational developers it is especially important to understand as a basis for the process of achieving goals. The goal is so that it can run as expected, something that is realized that describes a certain scope, in the implementation and supervision management manages all resources such as educators, costs, machines, markets, time, methods, materials, and all information to achieve the goals set. efficient. Education Management has the goal of forming the personality of students to fulfill the goals of education according to development or improvement based on educational goals, also to achieve educational goals and objectives. The aim of education management is also to educate the life of the nation and develop the whole person, as well as to become a human being who has faith and is devoted to God Almighty and has noble character, has broad knowledge and skills, is physically and spiritually healthy, has a strong and independent personality and has a sense of responsibility. social and national responsibility. Keywords: Management, Scope of Management, Education.